A review on the phytochemistry and pharmacology of the herb Scoparia dulcis L. for the potential treatment of metabolic syndrome. Issue 50 (22nd September 2021) - Jiang, Zikang; Sung, Jinghui; Wang, Xuyun; Zhang, Yangyang; Wang, Yaomiao; Zhou, Haifeng; Wen, Lei
Abstract : This review discusses the chemical constituents and pharmacological effects of S. dulcis plants. S. dulcis provides new potential for medicine and can be promoted as a complementary or alternative therapy for patients with chronic conditions. Abstract : This review discusses the chemical constituents and pharmacological effects of Scoparia dulcis L. ( S. dulcis ) plants. So far, approximately 160 compounds have been identified from S. dulcis, among which 115 compounds may be related to the treatment of metabolic syndrome. Extracts of S. dulcis have effects of reducing fasting blood glucose level, increasing the plasma insulin level, and stimulating insulin secretion to treat diabetes. They also produce antihyperlipidemic effects by increasing serum high-density lipoprotein levels, the anti-atherogenic index of plasma, and HMG-CoA reductase activity. The chemical composition of glutinol and glutinone, isolated from S. dulcis, provide potential anti-inflammatory effects. These compounds can also reduce total cholesterol, triacylglycerol, and low-density lipoprotein (LDL)-cholesterol and increase high-density lipoprotein (HDL)-cholesterol to provide the anti-atherosclerotic effect. S. dulcis exerts anti-arthritic properties through its effect on cytokine levels, significantly reducing IFN-γ and IL-6 levels and elevating IL-10 levels. The extracts carry out hepatoprotective effect by preventing the descent of the antioxidative enzymes of superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione reductase (GRd), and glutathione- S -transferase (GST). Therefore, S. dulcis provides new potential for medicine given its numerous therapeutic properties and can be promoted as a complementary or alternative therapy for patients with chronic conditions.